Potencialidades dos parques lineares na recuperação de áreas de fundos de vale - Barbosa, Leonardo Cassimiro (2010)
This research aims to demonstrate the potential and functions that the greenway can assume in the recovery of the valleys in a social, cultural and ecological level. The methodology consisted in a review of the current literature and an analysis of environmental legislation in order to base the research and develop a methodology for implementation of greenways along the water resources, that begins with the preparation of a previous scene to the valley with the greenway implanted, then it was made an investigation of the ecological and cultural variables of the corridor, after, it takes place a synthesis and diagnosis of this information collected through a holistic view, drawing up guidelines for recovery of the valley and implementation of the park and, finally, the elaboration of the final plan. As a case study, it was applied the method proposed to valley of Mandacarú stream in Maringá-PR city, an area degraded by human action. As a result, it was found that the greenway can assume an important role in assisting urban drainage, protection of natural resources, to combat illegal occupations, to instigate social cohesion and environmental education and also bring economic benefits to cities, with the landscape valuation. lt was verified the main environmental impacts that compromise the quality of the study area, as erosion, loss of riparian vegetation, illegal connections to sewers and lack of environmental education. Also, it was listed guidelines for restoration and conservation of the area, coupled with the deployment of a greenway. lt is hoped that the guidelines set can help a future intervention in place and that the proposed method is used for the recovery other valleys in cities.